PRODUCTIVITY OF UNIVERSITY HOSPITALS IN POLAND: A MALMQUIST-INDEX APPROACH - Rój, Justyna (Ekonomika, 2010)
The purpose of this article is to present the result of productivity analysis of university hospitals in Poland. The hospital sector, and especially the tertiary hospital subsector, are a large consumer of scarce health care resources, and it is of particular relevance to use these scarce resources as effectively and efficiently as possible. This is why it is so important to measure the efficiency and productivity of a hospital to find out whether it is still possible to improve their performance. In this paper, an analysis of 40 tertiary hospitals (which are called university hospitals in Poland) for the period from 2000 to 2007 is presented. To measure hospital productivity, the Malmquist index was employed. The usage of the Malmquist index is based on the data envelopment analysis (DEA), a non-parametric method to estimate the frontier functions, and this is a reason why this method was also employed in this research. The data comprise the number of physicians and nurses employed in university hospitals, the number of beds and the total number of bed days. The results show that in general there has been a worsening of the productivity of these hospitals over this period, and it was caused by an inappropriate usage of inputs. The paper is organized as follows: a brief description of hospital systems in Poland and the concept of their efficiency and productivity are presented, and then the method and data are discussed. In the fourth section, the results are presented, followed by conclusions.